Blockchain and IOT integrated Smart City Architecture (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recently, the concept of "Smart Cities" has been greatly improved with the growth and development of the Internet of Things as a new form of sustainable development. Smart cities rely on independent and distributed infrastructure that includes information processing and control systems, diverse network infrastructure, and ubiquitous sensitivity that includes millions of information sources. Due to the continued growth of data volume and the number of connected IoT devices, however, issues such as high delays, bandwidth barriers, security and privacy, and scalability emerge from the current smart city network construction. Designing an efficient, secure and scalable distributed architecture by bringing computer and storage resources closer to endpoint is needed to address the limitations of today’s smart city network. In this paper, we propose a hybrid network design for an intelligent city using the emerging technologies of Software Defined Networking and blockchain technology. To achieve efficiency and address current constraints, our paper is divided into two parts: the main network and the edge network. In this we proposed hybrid architecture which inherits the capability of both centralized and decentralized network integrated with proof of work for the security and privacy. To evaluate the feasibility and performance of our proposed model, we simulate our model and evaluate it based on various performance metrics. The result of the evaluation shows the effectiveness of our proposed model.